애양원(愛養園) 한센병 환자 자치조직의 형성과 공동체의 성격 변화(1910-1940) - 장민한; 유연실 (의료사회사연구, 10(0), 2022)
애양원은 1909년 광주에서 한센병 치료를 목적으로 설립된 나요양소를 모체로 한다. 광주 나요양소는1909년 선교사 포사이트가 나주 남평에서 발견한 한센병 환자를 광주로 이송하면서 치료를 시작했으며, 1912년11월 15일 한센병 환자 전문 수용기관으로 정식 개원하였다. 광주 나요양소는 1926년 도시민들의 반발로 여수 율촌면의 신풍반도로 이전하였다. 1962년 이후 애양원은 한센인 정착촌의 형성과 소아마비 중심의 진료체제로의 전환 속에서 환자공동체가 점차 해체된다. 애양원은 일제시기 기독교 나요양소의 대표적인 모델로서 환자 자치조직의 운영과 자활 노동을 통한 경제적 자립이 두드러진 특징으로 나타난다. 본고는 애양원의 환자 자치조직의 운영에 주목하여 크게 두 가지 측면을 중점적으로 검토하였다. 첫째, 애양원 환자자치조직과 교회 권력의 관계를 시기별로 검토하여, 환자공동체의 성격 변화를 고찰하였다. 애양원은 광주 나요양소시기(1910-1926), 여수 애양원 시기(1926-1934), 일심회 사건과 김응규 목사 퇴진 운동 이후 시기(1934-1940)까지의 역사적 변천 과정을 겪는 동안 그 성격이 ‘선교사 중심의 신앙공동체’에서 ‘환자 중심의 생활공동체’로 변화하였다. 이는 애양원이 운영지도부(병원ㆍ 교회)와 환자 자치조직의 관계에 따라 공동체의 성격이 변화했다는 것을 의미한다. 광주 나요양소의 환자 자치조직은 선교사의 지도하에 성장했으며, 환자들의 우두머리인 회장도 병원장에 의해 임명되었기 때문에 독립적인 권력을 형성하지 못했다. 1926년부터1934년까지는 집행위원회(부장회)를 중심으로 환자 자치조직이 성장하면서, 교회 권력과 자치조직이 서로 대립하는 일도 벌어졌다. 이는 1934년 반교회적 일심회 사건과 1938년 김응규 목사 퇴진 운동으로 표출되었다. 그러나 일심회 사건 이후 1936년 환자 자치조직이 재편되고, 병원장이 일부 집행위원에 대한 임명권을 확보한다. 이를 통해 병원장의 환자 자치조직에 대한 견제와 통제가 강화되고, 교회 권력과 환자 자치조직의 운영이 일원화되면서 신앙공동체적 성격이 회복된다. 둘째, 애양원 한센병 환자들의 주체성을 검토하였다. 애양원 내에서 환자들은 신앙을 통해 교회 권력에 접근하였고, 11개 부서(시기에 따라 변화)의 장을 환자들이 선출하여 집행위원회(부장회)를 구성하였다. 환자가 자치조직의 대표(집행위원/ 부장)를 직접 선출하여 애양원의 운영에 참여했다는 점에서, 환자들은 교회 권력에 대한 견제가 가능했다. 또한 환자들은 노동 자활을 통해 경제적 자립을 도모하고 가정사를 구축하여 가족단위의 삶을 영위할 수 있었다. 환자 자치조직의 자율성은 교회 권력의 견제 속에서 축소되기도 하였지만, ‘부장회’와 같은 환자 자치조직의 자율적 운영은 환자들이 ‘투표권’을 행사하며, 주체적 의사결정을 할 수 있는 중요한 경험을 제공했다. This paper focuses on the operation of autonomous organizations for patients at Aeyangwon(愛養園) to analyze the following two aspects. First, it studies the relationship between autonomous organizations and church power at Aeyangwon in different periods, and examines the changes in the characteristics of its patient community. Aeyangwon experienced several historical changes: Guangzhu Na(癩) Sanatorium Period (1910-1926), Yeosu Aeyangwon Period (1926-1934), and the Ilsimhoe(一心會) Incident and the Movement Period to force Pastor Kim Eung-gyu to step down (1934-1940). Its characteristics also changed from a “missionary-centered belief community” to a “patient-centered life community.” The characteristics of the patient community had changed according to the relationship between operation leadership (hospital and church) and autonomous organizations for patients. The autonomous organization at Guangzhu Na(癩) Sanatorium functioned under the leadership of missionaries, and the patient leader was also appointed by the president of the hospital; thus, the patients could not enjoy much independence. From 1926 to 1934, as the autonomous organization grew with Executive Committees at its center, opposition between the church power and the patients also occurred. This was manifested in the anti-church Ilsimhoe Incident in 1934 and the 1938 movement to force Pastor Kim Eung-gyu to step down. However, after the Ilsimhoe Incident, the autonomous patient organization was reorganized in 1936, and the hospital president earned the right to appoint two executive committee members. Through this process, the hospital president strengthened the containment and control of patients’ autonomy, and the characteristics of a belief community were restored as the church came to operate the patient organization. Second, this paper discusses the subjectivity of patients with Hansen’s disease at Aeyangwon. At Aeyangwon, the patients shared the power of the church by expressing their faith and directly elected ministers of 11 departments to form an executive committee. Through the direct election of representatives (executive committee members and ministers) of their autonomous organization, the patients participated in the operation of Aeyangwon and were able to resist the power of the church. In addition, the patients sought economic self-reliance through labor, built family houses, and maintained a family-based life. Although the autonomy of the patient organization had been reduced under the control of the church, patients used their voting rights to elect executive committee members and participated in the operation of their organization, which provided an institutional guarantee for the patients to exert their subjectivity. KCI Citation Count: 1